IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE PADA PT TIMAH TBK DALAM MENGELOLA RISIKO ENVIRONMENTAL, SOCIAL, AND GOVERNANCE - Mutyara Zahratu (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles at PT Timah Tbk. in managing high Environmental, Social, and Governance (ESG) risks. The sample selection technique uses purposive sampling with a focus on secondary documents in 2024 that are relevant to the ESG risk rating in 2025. The research method used is descriptive qualitative with a case study approach. Data were analyzed using content analysis methods and source triangulation to ensure the validity of the findings. The results showed that the implementation of GCG principles has been running well and plays a significant role in mitigating the company’s ESG risks, but there are still some weaknesses. The implications of this research emphasize the importance of maintaining and improving effective governance practices to support sustainability and optimal ESG risk management in state-owned companies.